MANAJEMEN KENDALA OPERASIONAL HOUSEKEEPING DAN IMPLIKASINYA PADA KUALITAS LAYANAN BEVERLY HOTEL BATAM - Handika Napitupulu; Andri Wibowo (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to analyze the management of operational constraints faced by the housekeeping department and its implications for service quality at Beverly Hotel Batam. The research employed a qualitative descriptive approach using a case-study method. Data were collected through direct observation, semi-structured interviews with one housekeeping Supervisor and several room attendants, including both permanent staff and daily workers, as well as supporting documentation. The data were analyzed using Miles and Huberman's interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the main operational constraints include limited workforce, inadequate cleaning equipment and supplies, heavy workloads, and low employee motivation. Management addressed these issues through regular training, direct supervision, and more balanced task distribution. Effective management of operational constraints has a positive impact on service quality, particularly in the reliability and responsiveness dimensions of the SERVQUAL model. The study emphasizes the managerial role in maintaining room cleanliness and guest satisfaction within the hotel industry.